The Evolution Of Non-Invasive Blood Glucose Monitoring System For Personal Application - Nurul Akmal, Abd Salam; Wira Hidayat, Mohd Saad; Zahariah, Manap; Fauziyah, Salehuddin (Penerbit Universiti, UTeM, 2016)
Glucose monitoring technology has been used by diabetic patients to monitor their blood glucose level for the past three decades. This technology is very useful for managing diet among diabetic patients. This paper reviews the fundamental technique of blood glucose detection method and the development of blood glucose monitoring systems that have been developed ever since. The most common and widely used technique is an invasive technique that requires users to prick their finger to draw the blood. However, recently a lot of new technologies have been developed for non-invasive technique to monitor blood glucose monitoring and studies in this area are growing rapidly. Among all, the optical and transdermal approach are the two most potential sensing modalities for non-invasive glucose monitoring that show a very good prospect.